What a difference a digraph made: phonetic spelling and the assimilation of the word “armada” in Early Modern English - Laetitia Sansonetti (Lexis: Journal in English Lexicology)
This article focusses on the joint evolution of the spelling and meaning of the word ‘armada’ to refer to a(n) (armed) fleet of ships in early modern English texts, from its first uses in translations of Latin and Italian texts in the first half of the sixteenth century to Gazophylacium Anglicanum, a 1689 English dictionary of hard words, which explains its Latin origins and calls it “a word purely Spanish”. Rather than a word biography, I try to write the aural story of ‘armada’ by considering its variations in spelling over the period: the ‑a/‑o substitution for the final vowel and the ‑t‑/‑d‑/‑th‑ substitution for the intervocalic plosive. The main argument is that these substitutions reflect the phonetic processes at work in English borrowings from Romance languages for nouns derived from past participles of first-group verbs, which have similar morphological features in Latin (‑atus), Spanish (‑ado), and Italian (‑ato), and for which French adaptations of these Italian or Spanish terms may also have played a part in spelling choices.